AutoCAD 2012 and AutoCAD LT 2012 essentials : AutoDesk official training guide - Onstott, Scott (Autodesk official training guide., 2011)
"AutoCAD Essentials is a unique learning resource that features concise, straightforward explanations and real-world, hands-on exercises and tutorials to teach new users the software's core features and functions. Each chapter opens with a quick discussion of concepts and learning goals and then briskly moves into approachable hands-on exercises that readers can follow to gain confidence using the software. Each chapter features compelling full-color screenshots to illustrate tutorial steps, and chapters conclude with related suggested exercises to further reinforce the chapter's lessons. Readers can download starting and ending files for the exercises = so that they can start anywhere in the book and compare their results with the pro's. This book introduces users to the software's interface and foundational concepts. Following a workflow-based approach that mirrors how projects progress in the real world, the book then guides readers through basic 2D drawing skills, editing entities, working with splines and polylines, controlling object visibility and appearance, and organizing objects. Readers are then shown how to best use hatches and gradients, work with blocks and Xrefs, create and edit text, do dimensioning, use constraints, work with layouts, print and plot, store and extract data, navigate and model in 3D, and present your design. Finally, the Certification Appendix assists readers in preparing for the Certified User, Certified Associate, and Certified Associate exams"--